Influência do capital psicológico na relação entre características habilitantes do orçamento, compromisso com as metas orçamentárias e o desempenho gerencial - Benin, Daiane Ana Gris (2024)
This study evaluated the influence of psychological capital on the relationships between budget enabling characteristics, commitment to budget goals and the managerial performance of professionals with budget responsibility in a multinational organization operating in Brazil. The research is classified as descriptive and explanatory, with a quantitative approach, carried out by means of a survey. The sample consisted of 85 mid-level managers with budgetary responsibility, in which the individual is the level of analysis, by analyzing the duality of budgetary controls (enabling or coercive), based on Social Cognitive Theory. The theoretical relationships investigated in this research were tested using the structural equation modeling technique. Budget management is highlighted in the literature as crucial in the organizational context, particularly the enabling characteristics of budgetary control, such as repair capacity, internal and global transparency and flexibility. The introduction of psychological capital added a psychological dimension to the discussion, showing how management practices, especially the enabling characteristics of budgetary control, can influence managers' mental and cognitive states. Social Cognitive Theory was used as theoretical support to explain the interaction between the factors analyzed. The results showed that flexibility had a direct and positive influence on psychological capital and managerial performance, but not a significant influence on commitment to budget targets. Internal transparency positively influenced commitment to targets and managerial performance, but had no significant impact on psychological capital. The ability to repair and global transparency were not significantly related to psychological capital, commitment to goals and managerial performance. The results indicate that flexibility contributes to a more positive work environment, promoting self-efficacy, hope, resilience and optimism in managers. Internal transparency facilitates commitment to targets, while repair capacity and global transparency proved to be less influential in this regard. Commitment to budget targets had a positive relationship with managerial performance and was a determining factor in its increase. Given these findings, we can conclude the importance of flexibility and internal transparency in the budget system analyzed, as a control mechanism that provides a more motivating and efficient working environment to boost managers' psychological capital and commitment to budget targets, which contributes to boosting their managerial performance. This study contributes to budget management by integrating new evidence from social and psychological aspects, which offer practical insights for organizations. It also highlights the importance of managers' well-being, in line with the Sustainable Development Goals, and encourages new research in management accounting. Recommendations include the exploration of unobserved variables, longitudinal studies, analysis in different sectors and cultures, the integration of 360-degree feedback and qualitative metrics to enrich the understanding of organizational dynamics and the use of enabling controls.